UNDERSTENDING OF RELIGIOUS AND ETHICAL UPBRINGING IN THE WORKS OF EAST ARMENIAN EDUCATORS (1840-1880) (Education in the 21st Century, 2023)
UNDERSTENDING OF RELIGIOUS AND ETHICAL UPBRINGING IN THE WORKS OF EAST ARMENIAN EDUCATORS (1840-1880)In the second half of the 19th  century,  there were many intellectuals, such as A. Bahatryan, I. Harutyunyan, S. Mandinyan, St. Fr. Mandinyan, Khoren Narpe, P. Shanshyan who received pedagogic higher education in advanced European institutions. Secular and spiritual educators distinguished four forms of education: mental, physical, labor, moral. Here, we have analyzed what concepts Armenian pedagogues have expressed under moral education, whether moral education is connected with religious education, what traditions the aforementioned Armenian pedagogues have followed. The aim of the research is to analyze the views of 19th  century Eastern Armenian educators regarding moral education. Find out which perception has been dominant in the field of public education. There are many sources related to the history of the Armenian school and pedagogical thought, but until now no in-depth studies have been conducted on the issue that interests us, as a result of which the history and methodology of moral education has remained uncertain.
Keywords: Pedagogue; education; East Armenian school; religious and ethical upbringing; the image and likeness of God